Curatorial Models and Strategies in a Digital Age - Czegledy, Nina . (Kepes, 2012)
This presentation is focused on the changing models of curatorial practice in general and then I will proceed to illustrated case studies of my own curatorial experience. Over the last decade, the progressively blurring boundaries between the different roles of art production and dissemination created an entirely new ecology where nearly every phase, every aspect, and every role embodied in art practice is radically changing. Rapidly emerging technologies contributed to this process. It has been also argued that truly contemporary work emerges at the point of exhibition, consequently the provisional nature of the ‘workshop lab in public’ or ‘lab as exhibition’ –a rapidly growing field- seems to keep the contemporaneity of the work alive in a particularly strong way. Today the role of the curator can be seen: ratorial selection, dissemination and audience reception, have shifted -beyond previously un-imagined settings and conditions. Today’s emphasis on the process rather than on the presented works is owing to the fact that in numerous cases the operating method- due to improvement in communication and presentation technologies- has changed, and I can’t repeat enough the word “change” in this context. A considerable amount of my references are based on the CRUMB or Curatorial Resource for Upstart Media Bliss mail list discussions and IDC or Institute for Distributed Creativity. I will freely quote from the relevant topics of these lists. In postings on this list a discussion ensued concerning analog and digital art.